Further Comment on "Smoothing" by Output Variation - McCain, Roger A. (Quarterly Journal of Economics, 1974)
Journal Article Further Comment on “Smoothing” by Output Variation Get access Roger A. McCain Roger A. McCain Western Washington State College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 88, Issue 3, August 1974, Pages 496–498, https://doi.org/10.2307/1881948 Published: 01 August 1974